Air Quality Characterization at Three Industrial Areas in Southern Italy - Perrino, Cinzia; Gilardoni, Stefania; Landi, Tony; Abita, Anna; Ferrara, Isabella; Oliverio, Serafina; Busetto, Maurizio; Calzolari, Francescopiero; Catrambone, Maria; Cristofanelli, Paolo; Dalla Torre, Stefano; Esposito, Giulio; et al. (Frontiers in Environmental Science, 2020)
Outdoor air pollution is responsible for more than 4 million premature deaths worldwide and its contribution is particularly severe in industrial contaminated sites, where epidemiological studies highlight often mortality rate larger than the national average. In the framework of the CISAS project, this study investigates spatial and temporal variability of air pollution across three industrial contaminated sites in southern Italy, classified as “High Risk Area of Environmental Crisis”: Crotone, Milazzo and Priolo. The environmental analysis employed three investigation approaches: - meteorological characterization of the sites with analyses of local air mass circulation; - statistical evaluation of the continuous measurements of gaseous pollutants and PM concentration; - determination of mass concentration and detailed speciation of the chemical components of atmospheric particulate matter during intensive field campaigns. Continuous trace gases and aerosol measurements (including NOx, SO2, O3, NMHC, PM10 and PM2.5) over the period 2016-2018 were analysed, and specific intensive field experiments (2016-2017), representative of winter and summer conditions, were carried out in order to determine PM10 and PM2.5 chemical composition. The analyses of PM components (ions, elemental composition, trace organic pollutants, organic carbon, and elemental carbon) show concentrations typical of rural and urban areas. The results concerning gaseous pollutants and PM concentration showed a general compliance of the concentrations of some regulated species with the limits set by the EU Ambient Air Quality (AAQ) Directive. However, in particular in the industrial areas of Milazzo and Priolo, the analysis here reported highlights the need for a stringent regulation on NMHC ambient concentration and composition, further investigation of fine particle composition and atmospheric processing, and a deeper understanding of the role of anthropogenic emissions on ozone formation, also considering the World Health Organization (WHO) limits.